Adherence thresholds of tenofovir diphosphate in dried blood spots for HIV treatment and pre-exposure prophylaxis: A scoping review - Mohammed K. Alghamdi; Mohammed W. Ali; Anel Schoonees; Tamara Kredo; Eric Decloedt; Roland van Rensburg (Southern African Journal of HIV Medicine, 2026)
Background: Tenofovir (TFV) is a key antiretroviral used in HIV pre-exposure prophylaxis (PrEP) and treatment, with efficacy contingent on adherence. Quantifying TFV concentrations in dried blood spots (DBS) as tenofovir diphosphate (TFV-DP) is a robust method for determining long-term adherence. However, standardised TFV-DP adherence thresholds in DBS have not been established. Objectives: To map the existing literature on TFV-DP concentration thresholds in DBS for assessing adherence to TFV-based HIV prevention and treatment, and to identify evidence gaps. Method: We conducted a scoping review in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. Eight electronic databases were searched for studies reporting TFV-DP concentrations in DBS in relation to adherence thresholds or clinical outcomes for TFV-based PrEP or antiretroviral therapy (ART). Pharmacokinetic simulation or modelling studies used as reference benchmarks were included. Data were screened and extracted by two independent reviewers. We conducted descriptive analysis, tabulating findings. Results: Twenty-two studies were included. TFV-DP adherence thresholds for PrEP and treatment varied widely, from ≥ 650 fmol/punch to ≥ 1850 fmol/punch, reflecting differences in study design, populations and ART formulations. Reference studies defined adherence threshold as ≥ 700 fmol/punch for four doses/week. PrEP studies reported TFV-DP concentrations of 993–1173 fmol/punch for 4–7 doses/week, indicating that the reference threshold was conservative. In treatment studies, concentrations ≥ 1250 fmol/punch were associated with virological suppression, whereas concentrations < 800 fmol/punch were linked to an increased risk of viraemia. Conclusion: This review of TFV-DP in DBS for HIV PrEP and treatment supports purpose- and population-specific thresholds and highlights the need for further threshold validation to optimise PrEP and treatment strategies.